Multiple carcinoid tumour of duodenum: an uncommon case - Patil, Vivek A.; Mahapatra, Bibekananda; Panchal, Anuraha; Deolekar, Sandesh R.; Patil, Soniya A. (International Journal of Research in Medical Sciences, 2017)
A 45 years old female patient with complaints of pain in epigastric region since 1 year not responding to proton pump inhibitors underwent oesophagogastroduodenoscopy which showed two duodenal masses. On further investigations diagnosis was duodenal carcinoid tumour. Patient underwent Pylorus Preserving Whipples surgery.